Comparison of Two Entry Methods for Laparoscopic Port Entry - Yadav, R. P.; Paudyal, N.; Bhattarai, A.; Adhikari, D. (Kathmandu University Medical Journal, 2021)
Background The first step in laparoscopic surgery is to establish the pneumoperitoneum for which many approaches have been introduced to minimize the complications. Although controversies exist regarding the most efficient technique, till now the best entry technique is still unsettled. Objective To compare the safety, operating time and outcome of Direct Trocar Insertion with a well-established and widely practised Open Access Technique. Method This is a prospective study at Nobel Medical College Teaching Hospital from November 2019 to February 2021. Patients were grouped into either of the two groups, Group 1 for Direct Trocar Insertion and Group 2 for Open Access Technique. They were later analysed for major and minor complications of the technique and a comparison of either method was done at the end of the study period. Result A total of 823 patients were enrolled in the study. Among the study population, 411 patients had Direct Trocar Insertion while 412 patients had Open Access Technique. The majority of the operation that was done during the study period was laparoscopic cholecystectomy. Patients in the Open Access Technique group experienced more complications compared to Direct Trocar Insertion group. Conclusion Despite the fear of adopting the Direct Trocar Insertion, this is a safe, better and quick technique for laparoscopic port entry. However, any surgeon practising laparoscopic surgery should be competent to adopt either technique to overcome failure in either process during port entry.